2012
DOI: 10.1017/s1368980012005046
|View full text |Cite
|
Sign up to set email alerts
|

Islamic fasting and weight loss: a systematic review and meta-analysis

Abstract: Objective: Studies on the effects of Ramadan fasting on weight changes have been contradictory. We brought together all published data to comprehensively examine the effects in a systematic review and meta-analysis. Design: Relevant studies were obtained through searches of PubMed and CINAHL and by independent screening of reference lists and citations without any time restriction. All searches were completed between October and November 2011. Setting: Changes in body weight during and after Ramadan were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 46 publications
12
111
2
5
Order By: Relevance
“…Across these studies, participant age ranged from 18 to 58; just over half (52%) were conducted in males and females, 34% were in males only and 11% were in females only. 26 The authors of this review found statistically significant weight loss in 21 (62%) of these studies. 26 When pooled, the studies in this meta-analysis showed a 1.24 kg weight reduction (95% CI −1.60, −0.88 kg) over the month of Ramadan fasting.…”
Section: Religious Fasting: Observational Researchmentioning
confidence: 82%
See 1 more Smart Citation
“…Across these studies, participant age ranged from 18 to 58; just over half (52%) were conducted in males and females, 34% were in males only and 11% were in females only. 26 The authors of this review found statistically significant weight loss in 21 (62%) of these studies. 26 When pooled, the studies in this meta-analysis showed a 1.24 kg weight reduction (95% CI −1.60, −0.88 kg) over the month of Ramadan fasting.…”
Section: Religious Fasting: Observational Researchmentioning
confidence: 82%
“…26 The authors of this review found statistically significant weight loss in 21 (62%) of these studies. 26 When pooled, the studies in this meta-analysis showed a 1.24 kg weight reduction (95% CI −1.60, −0.88 kg) over the month of Ramadan fasting. Across 16 follow-up studies, mean weight regain was 0.72 kg (95% CI 0.32, 1.13 kg) in the 2 weeks following Ramadan.…”
Section: Religious Fasting: Observational Researchmentioning
confidence: 82%
“…One major difference between human and rodent studies is that human subjects tend to behaviourally reduce food intake during TRF when permitted ad libitum/ self-selected intake (51,54) . Similarly, many Ramadan studies report a mild energy deficit, although this is not a universal finding (55,57) . Where energy restriction is absent, or minimal, current evidence suggests that TRF can influence metabolism (both positively and negatively), necessitating further study into the optimal fasting window (52,53) .…”
Section: Outstanding Questionsmentioning
confidence: 98%
“…Across these studies, participants' ages ranged from 18 to 58 years; just more than half (52%) of studies were conducted with both males and females, 34% were conducted with only males, and 11% were conducted with only females (86). The authors of the review found statistically significant weight loss in 21 (60%) of the studies (86). When pooled, the studies in this meta-analysis showed a 1.24 kg weight reduction [95% confidence interval (CI), −1.60 to −0.88 kg] during the month of Ramadan fasting.…”
Section: Ramadan Fastingmentioning
confidence: 99%